The Effectiveness of Blended Learning Approach with Student’s Perceptions in Control Systems Engineering Course - Ghazali, R.; Soon, C.C.; Has, Z.; Hassan, S.N.S.; Hanafi, D. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
This paper presents student’s perception and the effectiveness of blended learning in the control system engineering course. A sample size of 64 engineering students was selected to participate in this research works as a part of the third year engineering programme. Instead of a common face-to-face learning delivery approach, a blended learning approach is used in the evaluation process. Students responded to Likert-type surveys using the research instrument where the questionnaire that utilized to collect the research data contained three sections. Section one is conducted to identify general student’s demographic such as age, highest academic qualification and gender while section two consists of evaluation of the experiential data such internet experience, student technology access and proficiency status as factors that may influence student’s behaviour. Finally, section three in the instrument is performed to evaluate the student’s perception with blended learning that measured using the questionnaire item. Students expressed their response regarding the instrument item on a five-point scale from “Strongly Disagree” to “Strongly Agree”. Then, the effectiveness of blended learning in the engineering course in comparison with the traditional teaching approach is assessed with the ultimate goal of this approach is to develop and promote critical thinking where students will be able to learn through meaningful activities. The results of this research works support the expectation that blended learning approach offers meaningful learning and effective towards improving the student’s performance. As conclusion, the study showed that blended learning might potentially increase student’s motivation leading to better performance in the engineering education.